Pulmonary Tuberculosis and HIV/AIDS: joint space-time clustering under an epidemiological perspective - Nunes, Carla (2012)
Since the mid-80s Tuberculosis declining trend became softer and even reversed in some countries. HIV/AIDS frequently appears as the main cause for the resurgence of Tuberculosis. This work aims at identifying critical areas for the joint occurrence of these conditions in Portugal, and at confirming the belief that HIV is not a major explanation for the slow Tuberculosis incidence decline. Based on correlation analyses and space-time scan statistics, a weak statistical correlation between HIV and TB incidence rates were observed (0.279; p<0.001). For both diseases, Oporto and Lisbon Metropolitan Areas were identified as critical locals, with relative risks of, respectively, 1.77 and 1.78 for TB, and 5.66 and 3.31 for HIV. Similar areas were identified with a multivariate scan.